(untitled) (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Blessing with expected children is a cherished avenue. Nowadays, many couples use various methods with a view to getting certain sexed children. Prevention of genetic disease, desire for economic growth, attaining status and so forth lead a couple to struggle to conceive certain gender based child. There exists a variety of ways, by maintaining which; certain gender based child expectation process is followed. Among them, scientific method is the dominant one. This article in applying analytical method, tries to examine the legality of using this method-to what extent it complies with shari‘ah principles. Hence it presents the opinions of contemporary Islamic jurists while especially focusing on the judgment (fatwā) of Fiqh Academy, Mecca Mukarrama concerning this subject. Equipped with such more opinions, this paper attempts to explore the sharī‘ah standpoint with regard to the use of scientific method and thereby offers a guiding principle for scholars who want to talk about this issue. সারসংক্ষেপ : প্রত্যাশানুযায়ী সন্তান লাভ একটি আকাক্সক্ষার বিষয়। বর্তমান সময়ে অনেকে কাক্সিক্ষত লিঙ্গের সন্তান লাভের জন্য নানাবিধ পদ্ধতি অবলম্বন করে। বংশগত রোগের সংক্রমণ রোধ, অর্থনৈতিক সমৃদ্ধি লাভ, সামাজিক প্রতিপত্তির অধিকারী হওয়া ইত্যাদি বিভিন্ন উদ্দেশ্যে নির্দিষ্ট লিঙ্গের সন্তান প্রত্যাশা করা হয়। নির্দিষ্ট লিঙ্গের সন্তান নির্বাচনের বিভিন্ন পদ্ধতির মধ্যে বৈজ্ঞানিক পদ্ধতির শরয়ী বিধান বর্ণনার উদ্দেশ্যে এ প্রবন্ধটি রচিত হয়েছে। বিশ্লেষণমূলক পর্যালোচনা পদ্ধতিতে রচিত এ প্রবন্ধে উক্ত বিষয়ে সমকালীন উলামায়ে কেরামের মতামত, পক্ষ-বিপক্ষের দলীল-প্রমাণ ও এগুলোর পর্যালোচনা এবং ফিক্হ একাডেমি, মক্কা আল-মুকাররামার সিদ্ধান্ত তুলে ধরা হয়েছে। বক্ষ্যমাণ প্রবন্ধের আলোকে আলোচিত এ বিষয়টির স্বরূপ স্পষ্ট হবে এবং শরীয়া বিশেষজ্ঞদের জন্য এ বিষয়ে শরয়ী সমাধান প্রদান করা সহজ হবে বলে আশা করা যায়।